Inimputabilidade do Ezquisofrênico (REMUNOM, 2024)
Non-imputability is a legal concept that exempts the criminal liability of individuals who are unable to understand the illicit nature of their acts due to specific conditions, such as minority, mental illness or other disorders, such as schizophrenia. In the case of schizophrenia, which affects the perception of reality and thinking, recognition of non-imputability is essential to ensure that these people receive adequate medical treatment, instead of being criminally punished. Brazilian jurisprudence adopts the biopsychological system evaluating both the mental condition and the capacity of the agent at the time of the crime. For minors under 18 years of age, the biological system applies, assuming absolute non-imputability. Schizophrenia treatment involves medication and psychotherapy, and its diagnosis depends on rigorous psychiatric evaluations. Jurisprudence requires that incapacity be proven by medical reports at the time of the action. The goal is not only to protect the individual, but also to reduce stigma and ensure public safety by providing appropriate treatment.